E-modul ANALISIS PEMNFAATAN E-MODUL INTERAKTIF DALAM MENINGKATKAN KEMANDIRIAN BELAJAR SISWA SEKOLAH DASAR - Nita Dwi Rahayu April, Fingka Wahyu Anggraini, Rademptus Pulo Kelen, Hermawan Wahyu Setiadi (STKIP Subang, 2025)
This study aims to analyze the utilization of interactive e-modules in enhancing elementary school students’ learning independence. The research employs a qualitative approach through a literature study of various national publications discussing the effectiveness of interactive e-modules in elementary education. Data were collected from scientific articles published within the last decade that met the criteria of relevance to e-module implementation and self-regulated learning. The analysis reveals that interactive e-modules play a significant role in fostering students’ autonomous learning through multimedia features, free navigation, automatic quizzes, and instant feedback that facilitate reflection and self-evaluation. Moreover, interactive e-modules support the pedagogical shift from teacher-centered to student-centered learning by positioning students as active participants in the learning process. However, successful implementation is influenced by teachers’ readiness, students’ digital literacy, and the availability of technological infrastructure. Overall, this study concludes that interactive e-modules are an effective digital learning innovation for promoting self-regulated learning among elementary students and are highly relevant to the demands of 21st-century education. Keywords: Interactive E-module, Learning Independence, Elementary School, Digital Learning, Self-Regulated Learning.